2021
DOI: 10.3390/microorganisms9040800
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of SARS-CoV-2 Viral RNA in Nasopharyngeal Swabs after Death: An Observational Study

Abstract: The aim of this study was to investigate the persistence of SARS-CoV-2 in post-mortem swabs of subjects who died from SARS-CoV-2 infection. The presence of the virus was evaluated post-mortem from airways of 27 SARS-CoV-2 positive patients at three different time points (T1 2 h; T2 12 h; T3 24 h) by real-time PCR. Detection of antibodies to SARS-CoV-2 was performed by Maglumi 2019-nCoV IgM/IgG chemiluminescence assay. SARS-CoV-2 viral RNA was still detectable in 70.3% of cases within 2 h after death and in 66,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…In our study, the mean time between death and swab collection was 36 days (range 12–60) more than in other studies in which the persistence of viral RNA was observed in post-mortem collected swabs up to 128 h after death or in buried and exhumed corpses [ 73 , 74 , 75 , 76 ]. Swabs were analyzed by real time PCR, 42% of which were from moderate (27%) to highly positive (15%).…”
Section: Discussioncontrasting
confidence: 60%
“…In our study, the mean time between death and swab collection was 36 days (range 12–60) more than in other studies in which the persistence of viral RNA was observed in post-mortem collected swabs up to 128 h after death or in buried and exhumed corpses [ 73 , 74 , 75 , 76 ]. Swabs were analyzed by real time PCR, 42% of which were from moderate (27%) to highly positive (15%).…”
Section: Discussioncontrasting
confidence: 60%
“…3 The COVID-19 can cause mild symptoms or asymptomatic infections in at least 80% of patients but is potentially capable of causing acute respiratory distress in humans leading to death. 4,5 The median incubation period is 3 to 4 days (0-24 days). 6 The most common symptoms observed at the initial onset of the disease are a cough, fever, fatigue, difficulty in breathing, sore throat, headaches, conjunctivitis, and gastrointestinal/stomach upsets.…”
mentioning
confidence: 99%
“…The COVID-19 can cause mild symptoms or asymptomatic infections in at least 80% of patients but is potentially capable of causing acute respiratory distress in humans leading to death 4,5 . The median incubation period is 3 to 4 days (0–24 days) 6 .…”
mentioning
confidence: 99%
“…The viral load of nasopharyngeal swabs and sputum peaked at 5-6 days after onset (104-107 copies per mL), and even sputum samples taken 8 days after onset from patients who died were reported to have very high viral load (1-34 x 1011 copies/mL) (23) . SARS-CoV-2 ribonucleic acid (RNA) is detectable in nasopharyngeal swab uid from patients who died of coronavirus pneumonia in 70.3% of cases within 2 hours after death and 66.6% of cases within 24 hours after death (24) , and RNA was detectable in nasopharyngeal swab uid until 128 hours after death (25) . Regarding SARS-CoV-2 survival outside of the nasopharyngeal swab uid, RT-PCR on retinal samples from deceased patients with con rmed COVID-19 revealed viral RNA of SARS-CoV-2 in 3 of 14 eyes (26) , and PCR on vitreous uid 3 months after death detected coronal SARS-CoV-2 RNA (27) .…”
Section: Discussionmentioning
confidence: 99%